Research on key technologies of intelligent fully mechanized mining on working face with large mining height - FAN Jingdao (Gong-kuang zidonghua, 2018)
In order to solve problems of large number of workers and high labor intensity on fully mechanized mining face with large mining height, according to actual situation of No.2 Coal Mine of Huangling Mining Group Co., Ltd., technical difficulties such as precise control of rib spalling, soft bottom frame and equipment reliability, precision of perception and poor coordination in intelligent fully mechanized mining on working face with large mining height were analyzed. Technology route of visual remote intervention were used to realize intelligent normal mining of fully mechanized mining face with large mining height. Efficient coal mining technology, control technology of anti-rib spalling, intelligent control technology with soft bottom and broken roof were research focus. Mining efficiency of triangular coal is increased by 30% through mining process innovation; different control methods are used in different stages of rib spalling to control, and precise control of guard plate is achieved; intelligent processing under weak condition of soft bottom is completed through simulation of manual operation of descending of hydraulic support for several times, and the problem of coal piling in front of the support is solved; intelligent treatment under the condition of broken roof is completed by pulling support advanced to ensure that the roof broken area can be mined intelligently. The practice of No.2 Coal Mine shows that after adopting intelligent fully mechanized mining technology, intelligent production mode is realized which mainly based on intelligent operation of working face equipments and with the help of remote intervention control of monitoring center, as well as the “7+2” operation mode of 7 people underground and 2 people on the ground, so achieves the purpose of reducing staff and improving efficiency.